Experimental and theoretical investigation of drotaverine binding to bovine serum albumin - Gałęcki, Krystian; Courtade, Gastón; McFall, Aisling; Prieschl Teixeira, Renata; Grgic, Maja; Esteve-Sisteré, Marta; Maglemose Westphalen, Rikke (Biotechnology and Food Science, 2013)
This study was motivated by the need to provide more insight into the possible mechanism of the intermolecular interactions between antispasmodic drug drotaverine and one of the serum albumins (BSA), with the aim to indicate the most probable sites of these interactions. For this purpose both experimental (spectrofluorometric titration at various temperatures) and theoretical (molecular mechanics) methods have been applied. The obtained results clearly showed that drotaverine quenched BSA fluorescence, and the most probable mechanism is static quenching. The negative value of the theoretically predicted binding free Gibbs energy (-23.8 kJ/mol) confirmed the existence of the intermolecular interactions involving drotaverine and one tryptophan within BSA protein and was well agreed with the experimentally determined value of -25.2 kJ/mol.